On the design of deterministic dielectrophoresis for continuous separation of circulating tumor cells from peripheral blood cells. Issue 10 (25th February 2019) - Aghaamoo, Mohammad; Aghilinejad, Arian; Chen, Xiaolin; Xu, Jie
Abstract: Detection and analysis of circulating tumor cells (CTCs) have emerged as a promising way to diagnose cancer, study its cellular mechanism, and test or develop potential treatments. However, the rarity of CTCs among peripheral blood cells is a big challenge toward CTC detection. In addition, in cases where there is similar size range between certain types of CTCs (e.g. breast cancer cells) and white blood cells (WBCs), high‐resolution techniques are needed. In the present work, we propose a deterministic dielectrophoresis (DEP) method that combines the concept of deterministic lateral displacement (DLD) and insulator‐based dielectrophoresis (iDEP) techniques that rely on physical markers such as size and dielectric properties to differentiate different type of cells. The proposed deterministic DEP technology takes advantage of frequency‐controlled AC electric field for continuous separation of CTCs from peripheral blood cells. Utilizing numerical modeling, different aspects of coupled DLD‐DEP design such as the required applied voltages, velocities, and geometrical parameters of DLD arrays of microposts are investigated. Regarding the inevitable difference and uncertainty ranges for the reported crossover frequencies of cells, a comprehensive analysis is conducted on applied electric field frequency as design's determinant factor. Deterministic DEP design provides continuous sorting of CTCs from WBCs even with similar size and has the future potential for high throughput and efficiency.